An ultra-clean firn core from the Devon Island Ice Cap, Nunavut, Canada, retrieved using a titanium drill specially designed for trace element studies - Zheng, Jiancheng; Fisher, D.; Blake, E.; Hall, G.; Vaive, J.; Krachler, Michael; Zdanowicz, C.; Lam, J.; Lawson, G.; Shotyk, William (Journal of environmental monitoring, 2006)
An electromechanical drill with titanium barrels was used to recover a 63.7 m long firn core from Devon Island Ice Cap, Nunavut, Canada, representing 155 years of precipitation. The core was processed and analysed at the Geological Survey of Canada by following strict clean procedures for measurements of Pb and Cd at concentrations at or below the pg g−1 level. This paper describes the effectiveness of the titanium drill with respect to contamination during ice core retrieval and evaluates sample-processing procedures in laboratories. The results demonstrate that: (1) ice cores retrieved with this titanium drill are of excellent quality with metal contamination one to four orders of magnitude less than those retrieved with conventional drills; (2) the core cleaning and sampling protocols used were effective, contamination-free, and adequate for analysis of the metals (Pb and Cd) at low pg g−1 levels; and (3) results from 489 firn core samples analysed in this study are comparable with published data from other sites in the Arctic, Greenland and the Antarctic.
Gesehen am 29.09.2020